Study of the pharmacokinetics of antituberculosis drug Biomairin - Sh. A. Shomurotov; E. M. Sultanova; M. K. Salakhutdinova; U. J. Ishimov; J. F. Ziyavitdinov; O. N. Veshkurova; A. S. Turaev (LLC "Publisher OKI", 2018)
Resume. The results of a studying the pharmacokinetics of the anti-tuberculosis drug Biomayrin in experimental animals (rats) after oral administration were presented. A comparative analysis of the pharmacokinetic parameters of Biomayrin with a comparing drug (a mixture of rifampicin, ethambutol and isoniazid) showed that the bioavailability of isoniazid increased four times as a part of Biomayrin, the ethambutol and rifampicin three times compared to the comparing drug, thereby showing a prolonged effect. It should also be noted that the introduction of isoniazid into the polysaccharide matrix retards its metabolism to the therapeutically inactive acetylisoniazid.